Kapabilitas Auditor Internal pada Early Warning dalam Mendeteksi Potensi Kecurangan (Fraud) - Fitriadi, Fitriadi; Muhammad Reza Ramdani (Akubis : Jurnal Akuntansi dan Bisnis, 2024)
Research aims to test the auditor internal's expertise in early warning at Bank Syariah Indonesia KC Makassar 2. The independent variable used is the auditor internal's expertise while the dependent variable used is the fraud early warning system. The data in this research was obtained from Bank Syariah Indonesia KC Makassar 2 who were willing to be respondents. The results of this research indicate that the auditor internal's skill variable has a positive and significant effect on the fraud early warning system variable.